Miracle [videorecording (DVD)] - O'Connor, Gavin; Russell, Kurt; Clarkson, Patricia (Disney DVD : Distributed by Buena Vista Home Entertainment, 2004)
Based on the true story of the most famous team in the history of American sports: the 1980 U.S. Olympic hockey team. Follow from the team's selection process to the ultimate victory over Finland for the gold.